2018
DOI: 10.1007/s00391-018-1431-7
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility of the lifestyle integrated functional exercise concept in cognitively impaired geriatric rehabilitation patients

Abstract: In this group of moderately cognitively impaired rehabilitation patients the exercises were feasible mostly under supervised conditions and frequently included additional physical support. An adjustment of the LiFE exercises in this setting is required before a trial should be performed in the acute care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It starts with three weekly face-to-face sessions in the first month and ends with one weekly face-to-face session and one phone call biweekly in the last month and finally only two phone calls in the last week (Almeida et al, 2020). Belala et al (2019a) took a first step to develop an early rehabilitation and transitional care intervention for people with dementia in acute care (diaLiFE). They investigated the feasibility and acceptability of the original LiFE exercise framework in cognitive impaired people in a clinical setting.…”
Section: Life For Older Adults With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It starts with three weekly face-to-face sessions in the first month and ends with one weekly face-to-face session and one phone call biweekly in the last month and finally only two phone calls in the last week (Almeida et al, 2020). Belala et al (2019a) took a first step to develop an early rehabilitation and transitional care intervention for people with dementia in acute care (diaLiFE). They investigated the feasibility and acceptability of the original LiFE exercise framework in cognitive impaired people in a clinical setting.…”
Section: Life For Older Adults With Disabilitiesmentioning
confidence: 99%
“…Numerous other measurements (e.g., upper and lower limb muscle strength) also showed no effect (Almeida et al, 2021). Belala et al (2019a) recruited 20 inpatients from a subacute geriatric rehabilitation center with mild to moderate cognitive impairment. In this pilot study, they found a good acceptance rate for the overall activity framework in cognitive impaired people in a clinical setting.…”
Section: Life For Older Adults With Disabilitiesmentioning
confidence: 99%
“…One approach could be characterized by specific efforts to decrease the length of stay in patients with dementia and subsequent outpatient care including instructions on adapted physical exercise for this population, e.g. lifestyle integrated functional exercise [5]. Alternatively, the concept of early inpatient rehabilitation, which includes among other components, physiotherapy, occupational therapy, neuropsychology and logopedics and which is widely applied in German geriatric hospital patients, may need modification reflecting the specific needs of PwD and delirium.…”
Section: Dementia In Hospital Patientsmentioning
confidence: 99%